Network management services based on the OpenFlow environment - Wilk, Paweł; Nawrocki, Piotr (Computer Science, 2014)
The subject of this article is network management through web service calls, which allows software applications to exert an influence on network traffic. In this manner, software can make independent decisions concerning the direction of requests so that they can be served as soon as possible. This is important because only proper cooperation including all architecture layers can ensure the best performance, especially when software that largely depends on computer networks and utilizes them heavily is involved. To demonstrate that the approach described above is feasible and can be useful at the same time, this article presents a switch-level load balancer developed using OpenFlow. Client software communicates with the balancer through REST web service calls, which are used to provide information on current machine load and its ability to serve incoming requests. The result is a cheap, highly customizable and extremely fast load balancer with considerable potential for further development.